2019
DOI: 10.3892/ijo.2019.4823
|View full text |Cite
|
Sign up to set email alerts
|

Cystathionine‑γ‑lyase promotes the metastasis of breast cancer via the VEGF signaling pathway

Abstract: The present study aimed to provide data to support the association between cystathionine-γ-lyase (CSE) and breast cancer metastasis. Reverse transcription-quantitative polymerase chain reaction, immunohistochemistry and western blot analysis were used to detect the mRNA and protein expression levels of CSE in human breast cancer tissues and cells. MTS and 5-ethynyl-2′-deoxyuridine assays were used to assess cell viability and proliferation. Scratch wound and Transwell assays were conducted to determine cell mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 25 publications
0
45
0
Order By: Relevance
“…Wnt signaling pathway is one of the key cascades regulating cancer progression, and has been reported to play an important role in metastasis of many tumors including HCC, non-small cell lung cancer and colorectal cancer ( Lin et al, 2017 ; Yang et al, 2017 ; Zhang et al, 2018 ). Recent observations suggest that VEGF signaling pathway might promote tumor metastasis in many tumors including gastric cancer, HCC and breast cancer ( Zhang et al, 2017 ; Chen et al, 2019 ; Wang et al, 2019 ). Nuclear factor-kB (NF-κB) activated signaling pathway have been linked with proliferation, angiogenesis, invasion and metastasis in many tumors including breast cancer, prostate cancer and HCC ( Sung et al, 2008 ; Liu et al, 2015 ; Ren et al, 2017 ; Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling pathway is one of the key cascades regulating cancer progression, and has been reported to play an important role in metastasis of many tumors including HCC, non-small cell lung cancer and colorectal cancer ( Lin et al, 2017 ; Yang et al, 2017 ; Zhang et al, 2018 ). Recent observations suggest that VEGF signaling pathway might promote tumor metastasis in many tumors including gastric cancer, HCC and breast cancer ( Zhang et al, 2017 ; Chen et al, 2019 ; Wang et al, 2019 ). Nuclear factor-kB (NF-κB) activated signaling pathway have been linked with proliferation, angiogenesis, invasion and metastasis in many tumors including breast cancer, prostate cancer and HCC ( Sung et al, 2008 ; Liu et al, 2015 ; Ren et al, 2017 ; Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in gastric cancer, VEGF expression is also correlated with TNM staging and lymph node metastasis 38 . Moreover, distant metastasis and poor prognosis are related to VEGF in osteosarcoma, ovarian cancer and breast cancer 39 - 41 . In this study, we found that silencing VEGF inhibited NPC cell migration and invasion, and our in vivo study also illustrated the correlation of VEGF with cell proliferation and lung metastasis in NPC.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer metastases, CSE behaved as a positive regulator of VEGF-A expression and induced the PI3K/AKT, FAK-paxillin, and RAS-MAPK-ERK1/2 pathways. Overexpression of CSE also increased the levels of MMP2 and MMP9 in early metastatic breast cancer cells, allowing the degradation of the ECM and consequently the entering of tumor cells into the blood circulation [232].…”
Section: Tumor Type Metastatic Sites Vegfr-1 Ligands Vegfr-1mentioning
confidence: 96%
“…Breast Bone, lung, liver, and brain -The VEGF-A-stimulated-PKC pathway induces a pre-metastatic destabilization of pulmonary tight junctions, promoting vessel permeability and extravasation [225] -VEGF-A is involved in breast cancer liver metastases [227] -MiR-126 overexpression in human breast cancer inhibits cell proliferation by reducing VEGF-A levels [228] -Overexpression of COX-2-induced miR526b and miR655 in tumor cells upregulates VEGF-A [229] -VEGF-A signaling pathway and MMPs expression are positively regulated by cystathionine -γ-lyase, a key enzyme in the biosynthesis of the proangiogenic H 2 S [232] -PlGF stimulates cancer cell motility through activation of intracellular signaling cascades, including ERK1/2, and cytoskeletal remodeling [233] -PlGF favors CD34 + differentiation into tumor-mobilized bone marrow-derived CD11b + myeloid cells [235] -In breast cancer cells overexpression of COX-2-induced miR526b and miR655 results in upregulation of VEGFR-1 [229] -VEGFR-1 signaling, due to PlGF interaction, is associated with obesity-induced breast cancer progression [77] Ovary Peritoneum, liver, lymph nodes, bone, and brain -High expression of VEGF-A is considered a prognostic factor [239] -VEGF-A contributes to the recruitment and activation of myeloid-derived suppressor cells [242] -PlGF is overexpressed and increases MMP7 expression via downregulation of miR-543 [243] -PlGF overexpression increases ZEB2 expression in a p38 MAPK-dependent manner [245] -sVEGFR-1 induces cell death in a murine model of ovarian cancer [246] -VEGF-A is highly expressed in specimens from patients with post-radiotherapy relapsed/persistent cancer [250] -VEGF-A is coexpressed with a metabolism-related protein (MCT4 isoform) [251] -PlGF induces EMT, promoting migration and metastases, through activation of the ERK/MAPK signaling pathway [252] -VEGF-A in culture supernatants from cervical cancer cell lines induces an M2-like phenotype [254] -High VEGFR-1 expression is associated with distant metastases, poor OS and PFS [248] -VEGFR-1 is highly expressed in specimens from patients with post-radiotherapy relapsed/persistent cancer [250] Prostate Bone, lymph nodes, lung, liver, brain -VEGF-A expression and tumor invasiveness are favored by an acidic environment, through increased MMP9 secretion [256] -VEGF-A expression is higher in prostate cancer samples than in BPH and HGPIN samples [259] -VEGF-A decreases the expre...…”
Section: Tumor Type Metastatic Sites Vegfr-1 Ligands Vegfr-1mentioning
confidence: 99%